The genital area of Halacaridae (Acari), life stages and development of morphological characters and implication on the classification - Bartsch, Ilse (Zootaxa, 2015)
The genital region of juvenile and adult halacarid genera is described. Larvae are expected to be present in all, protonymphs at least in the majority of the genera. Two of the marine genera have three nymphal instars, in the others one or two nymphal instars are suppressed. Adults of marine species have one, two or three pairs of genital acetabula; intrageneric differences in the number of acetabula are present but rare. Derived from the number of perigenital setae and genital acetabula, in most genera it is the deutonymph which is suppressed, in a few others the tritonymph. Adults of species with two nymphal stages have either two or three pairs of acetabula, those with a single nymphal stage have either one or two pairs of acetabula. Two genera may lack the protonymphal stage, but more material is needed to prove the absence. The present-day classification is outlined and supplemented. Anomalohalacarus and Arenihalacarus are both assigned to the Anomalohalacarinae. The Halixodinae include Agaue, Bradyagaue and Halixodes, the knowledge of Australacarus and Colobocerasides is sparse, but they may have to be incorporated in the Halixodinae. The subfamily Halacarinae includes a single genus, namely Halacarus.